ĐA DẠNG THÀNH PHẦN LOÀI HỌ CÁ MÚ (Serranidae) VÀ GHI NHẬN BỔ SUNG CHO MỘT SỐ KHU VỰC BIỂN, ĐẢO VIỆT NAM - Trần, Văn Đạt; Vũ, Quyết Thành; Trần, Công Thịnh; O. V., Savinkin (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SPECIES DIVERSITY OF GROUPER (Serranidae) AND NEW RECORDS FOR THE GROUPER CHECKLIST OF VIETNAMESE WATERSFish species surveys conducted in areas of seas and islands including Namyit Island (đảo Nam Yết), Alison Reef (đá Tốc Tan), Tho Chu Island, Cat Ba Island, the coastal zone of Phu Yen province during the period 2020-2022 have recorded 33 species belonging to 11 genera of family Serranidae. In which, Namyit Island has the highest number of species of grouper with a total of 16 species belonging to 8 genera. Genus Epinephelus and Cephalopholis are the most diverse ones with 11 species (accounting for 33.3%). There is a difference in classification of species composition in different survey areas including remote islands of Spratly Islands (Truong Sa Islands) (Namyit Island, Alison Reef) and coastal zones (Tho Chu Island, Cat Ba Island, the coastal zone of Phu Yen province). Of the 33 species of grouper that have been recorded, 02 species (Gracila albomarginata (Fowler & Bean, 1930), Serranocirrhitus latus Watanabe, 1949) are founded to be new to the grouper fauna of Vietnam and 01 species (Anyperodon leucogrammicus (Valenciennes, 1828)) had been listed in the Vietnam's Red Data Book (2007) as Vulnerable (VU).